2018
DOI: 10.1016/j.bj.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of diabetic ketoacidosis, severe hypoglycemia and glycemic control among children and young adults with type 1 diabetes mellitus treated with premixed versus basal-bolus insulin therapy

Abstract: BackgroundThis study compared event rates of diabetic ketoacidosis (DKA) and severe hypoglycemia, as well as glycemic control, among children, adolescents, and young adults with type 1 diabetes mellitus (T1DM) receiving basal-bolus or premixed insulin therapy.MethodsA total of 825 individuals aged ≤ 20 years with T1DM, using either basal-bolus or premixed insulin regimens, were retrospectively recruited from 2001 to 2015. Rates of DKA after diagnosis, severe hypoglycemia, and the level of glycated hemoglobin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Basal bolus insulin regimen as a form of intensive insulin therapy has been found to be superior to conventional mixed insulin regimen. [16][17][18] In this study neither regimens had a significant effect on diabetic control, most likely because the study sample had a poor diabetic control generally in both groups, an important factor in this regard is that, basal bolus insulin regimen needs high level of education and training, because the flexibility in daily insulin dosage, according to dietary intake and blood sugar parameters, is the main advantage of this regimen over the twice daily regimens, this necessitates multiple daily decision making, needing appropriate training and mathematical skills, demanding a sufficient number of diabetic educators and dietitians in every diabetic center, a factor not sufficiently available in this study setting. The importance of education resonates well with the finding that maternal education had a significant effect on diabetic control in this cohort (P-value; 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…Basal bolus insulin regimen as a form of intensive insulin therapy has been found to be superior to conventional mixed insulin regimen. [16][17][18] In this study neither regimens had a significant effect on diabetic control, most likely because the study sample had a poor diabetic control generally in both groups, an important factor in this regard is that, basal bolus insulin regimen needs high level of education and training, because the flexibility in daily insulin dosage, according to dietary intake and blood sugar parameters, is the main advantage of this regimen over the twice daily regimens, this necessitates multiple daily decision making, needing appropriate training and mathematical skills, demanding a sufficient number of diabetic educators and dietitians in every diabetic center, a factor not sufficiently available in this study setting. The importance of education resonates well with the finding that maternal education had a significant effect on diabetic control in this cohort (P-value; 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…32 It's a controversial issue whether premixed insulin therapy has a poor control of HbA1c and increases DKA occurrence rate compared to MDI in T1DM. 33 Other T1DM patients may integrate traditional Chinese medicine to reduce the risk of diabetic ketoacidosis in patients with type 1 diabetes mellitus. 34 Also, it was reported that 5% patients may withdraw insulin therapy inappropriately during honeymoon period.…”
Section: Accessibility Of Insulinmentioning
confidence: 99%
“…Premixed insulin therapy with injections twice daily is also administered among part of T1DM children 32 . It's a controversial issue whether premixed insulin therapy has a poor control of HbA1c and increases DKA occurrence rate compared to MDI in T1DM 33 . Other T1DM patients may integrate traditional Chinese medicine to reduce the risk of diabetic ketoacidosis in patients with type 1 diabetes mellitus 34 .…”
Section: Progress In Management Of Pediatric Diabetes In Chinamentioning
confidence: 99%
“…In this issue of the Biomedical Journal , Chou et al. [1] examine a long history of cases of TD1 to determine whether different injection/dosing regimes influence the risk of developing serious complications of the disease.…”
Section: Spotlight On Original Articlesmentioning
confidence: 99%
“…To shed light on the issue, Chou et al. [1] carry out a large retrospective review of patients with TD1 recorded in a Taiwanese registry.…”
Section: Spotlight On Original Articlesmentioning
confidence: 99%